Biological variation of serum canine calprotectin concentrations as measured by ELISA in healthy dogs. (May 2019) - Heilmann, R.M.; Ruaux, C.G.; Grützner, N.; Cranford, S.M.; Bridges, C.S.; Steiner, J.M.
Highlights: Calprotectin is a useful biomarker of inflammation in dogs. At least a moderate change in serum calprotectin is needed to be considered as relevant. A population-based reference interval may or may not be appropriate for serum calprotectin. The ELISA-reference interval for serum calprotectin concentration is 0.6–11.8 mg/L. Abstract: Calprotectin is a useful biomarker of inflammation in dogs. However, the biological variation of serum canine calprotectin is unknown. Indices of biological variation were determined in serial serum samples (n = 147) from 11 healthy dogs (males/females: 4/7, median age: 5 years): analytical (3.0%), intra-individual (29.9%), and inter-individual variation (33.2%), reciprocal index of individuality (1.1), and index of heterogeneity (4.9). Serum calprotectin concentrations measured by ELISA and by the previous radioimmunoassay were highly correlated, but a constant and proportional bias exists between both assays. A de novo ELISA-reference interval (RI) for serum calprotectin concentration was established (0.6–11.8 mg/L). Moderate changes in serum calprotectin (minimum critical difference: 6.4 mg/L) between sequential measurements are needed to be considered relevant, and a population-based RI may or may not be appropriate for serum calprotectin.